Business Intelligence Concepts for Education Quality Management - Nycz, Małgorzata; Owoc, Mieczysław L.; Pondel, Maciej (Koncepcja wykorzystania inteligencji biznesowej w obszarze zarządzania jakością kształcenia, 2010)
On the one hand, there is a lack of applications within the basic areas of business intelligence applications, especially in education sector. On the other, we observe the real need of permanent improvement the education quality in modern universities. The main goal of the paper is to present our concept for improving the education quality in higher education using modern IT. To obtain this we have carried out analysis of the BI usability focused on education quality at the university level. In the context of managerial decision support, we have shown some BI features and then presented the model of data warehouse for this purpose. Next the discussion on exploration techniques in the Oracle environment as well as its adequacy has been presented. Short summary ends the paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 47-59
Keywords: business intelligence; education quality management; data mining